Sublethal heat treatment enhances lactic acid uptake in macrophages via MCT1, leading to reduced paraspeckle formation and a subsequent decrease in macrophage pyroptosis - Fan, Zhuoyang; Yang, Guowei; Luo, Rongkui; Qu, Xudong; Ye, Xiaodan; Wang, Jianhua; Yan, Zhiping; Shu, Minfeng; Zhang, Wei; Liu, Rong (Frontiers in Immunology, 2024)
This study offers a comprehensive analysis of cellular dynamics, metabolic shifts, and macrophage polarization in the tumor microenvironment post sublethal heat treatment. A marked acidification was observed in the tumor cell supernatant, attributed to an increase in lactic acid production. This pH shift, pivotal in tumor progression and resistance, also played a crucial role in guiding macrophage polarization, notably towards an M2 phenotype known for its tumor-promoting functions. Elevated lactic acid concentrations in co-culture mediums reinforced its role as a polarizing influencer. Furthermore, an upregulated expression of MCT1 after sublethal heat treatment highlighted its central function in lactic acid transport, leading to a relative acidic microenvironment and M2 macrophage polarization. Intriguingly, a lack of significant disparity in MCT1 expression between hepatocellular carcinoma patients and healthy liver tissues underscores the multifaceted nature of cancer biology. Additionally, the observed interrelation between pyroptosis, lactic acid, MCT1, and the inhibition of macrophage pyroptosis presents profound implications for therapeutic strategies targeting the tumor immune environment. The association of paraspeckle (a form of phase separation) with macrophage dynamics in HCC introduced another layer of complexity. Post sublethal heat treatment, the reduction of paraspeckle particles under lactic acid exposure suggests diverse cellular impacts. The study also identified PKM2 as a pivotal molecule in this interplay, showing decreased levels after sublethal heat treatment in conjunction with lactic acid exposure. Collectively, these findings shed light on the intertwined mechanisms of sublethal heat treatments, metabolic alterations, and immune modulation in the tumor milieu.